Delayed access to bunion correction surgery: Are patient-reported outcomes affected?. Issue 3 (14th September 2018) - Wing, Kevin; Sutherland, Jason; Younger, Alastair; Veljkovic, Andrea; crump, Trafford; Liu, Guiping
Category: Bunion Introduction/Purpose: Little is known about the effect of delayed access to bunion correction (Hallux Valgus) surgery on patient-reported outcomes. The objective of this study is to measure the association between delayed access to bunion correction surgery and post-operative patient-reported outcomes. Methods: This study prospectively recruited patients to complete pre-operative patient-reported outcomes measuring pain, depression and foot and ankle health. Patients complete the same patient-reported outcomes six months post-operatively. Linear regression models measured outcomes, adjusting for baseline health, age category, sex, comorbidities and socio-economic status. Results: This study included 74 participants, a response rate of 53% among eligible patients. Among participants, 58.9% underwent a Lapidus procedure, the remainder underwent a corrective osteotomy. There was no relationship between post-operative depression and pain scores with duration of wait time, adjusting for patient characteristics. Longer waits for bunion correction surgery, adjusting for other factors, were associated with smaller gains in health in four of the five domains of measurement of foot and ankle health. Conclusion: At the six-month post-operative time point, prolonged wait times were detrimental to foot and ankle outcomes in four of the five domains of the foot and ankle specific PRO. Policies for expediting access for symptomatic hallux valgus are warranted to mitigate poorer long-term outcomes.